(untitled) - Peter Bromhead (Essex, 1998)
This book is a introductory discussion of British life and institutions and is intended for advanced students of English. It takes account of the social, economic and political changes which have occured in Britain during the late 1980s and early 1990s. Tables and charts have been included, together with questions for students to consider.
Keywords: english language - textbooks for foreign speakers,gt. britain - social conditions